2013
DOI: 10.1073/pnas.1311000110
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Eph receptor tyrosine kinase activation from crystal structures of the EphA4 ectodomain and its complex with ephrin-A5

Abstract: Eph receptor tyrosine kinases and their ephrin ligands mediate cell signaling during normal and oncogenic development. Eph signaling is initiated in a multistep process leading to the assembly of higher-order Eph/ephrin clusters that set off bidirectional signaling in interacting cells. Eph and ephrins are divided in two subclasses based on their abilities to bind and activate each other and on sequence conservation. EphA4 is an exception to the general rule because it can be activated by both A-and B-class ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 33 publications
8
73
0
Order By: Relevance
“…28 and the Human Protein Reference Database [HPRD], http://www.hprd.org), sheds light on its novel role in ligand-mediated TEK receptor activation. The FN3 domain in the Eph family tyrosine kinase receptors directly stimulates intermolecular interactions to cluster the receptor into higher-order multimers at the plasma membrane (56). These Eph clusters act as efficient signaling centers to trigger cell responses and propagate phosphotyrosine signals.…”
Section: Discussionmentioning
confidence: 99%
“…28 and the Human Protein Reference Database [HPRD], http://www.hprd.org), sheds light on its novel role in ligand-mediated TEK receptor activation. The FN3 domain in the Eph family tyrosine kinase receptors directly stimulates intermolecular interactions to cluster the receptor into higher-order multimers at the plasma membrane (56). These Eph clusters act as efficient signaling centers to trigger cell responses and propagate phosphotyrosine signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nature of the impaired interactions remains elusive, the disease-causing mutation supports the evidence for the Fn2-mediated Tie2 clustering. Similarly, in the Eph family tyrosine kinase receptors, the membrane-proximal Fn-like domains are known to stimulate intermolecular interactions (45).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic studies of closely related EphA2 and EphA4 receptors identified a leucine zipper-like interface in the CRD comprised of hydrophobic residues that mediates EphA clustering in the plasma membrane (31,41,47,53) and an additional LBD interface that promotes large-scale multimerization of EphA2 (31, 47, 53). EphA3 has not been crystallized, but the LBD interface involved in EphA2 dimerization is highly conserved in EphA3 (31).…”
Section: Discussionmentioning
confidence: 99%
“…To more finely map the interaction determinants at the amino acid level, molecular modeling was performed using the ClusPro server (40) to analyze docking between rat NCAM Ig1-3 (PDB code 1QZ1) (38) and mouse EphA3 LBD/CRD modeled on human EphA4 (PDB code 4M4P) (41). Docking poses were screened for compatibility with interaction on the surface of a membrane in a cis conformation, lack of steric hindrance between additional domains of the molecules, and the number of hydrogen bonds within the interaction interface.…”
Section: The Ig2 Domain Of Ncam Binds the Cysteine-rich Domain Of Ephmentioning
confidence: 99%